Analisis Determinasi Profitabilitas Perusahaan Distrik Pertambangan - Bayu Hilmi Rachmaddian; Erna Sulistyowati (Journal of Management and Bussines (JOMB), 2023)
The research aims to empirically test the influence of cash turnover and receivables turnover on profitability in mining companies listed on the IDX in 2019-2021. This study method is quantitative using multiple linear regression analysis techniques with the help of the SPSS 25 program. This study uses side purposive with a total sample of 39 study data. The results of the research show that cash turnover partially has no effect on profitability, partial receivables turnover has an effect on profitability, and partial inventory turnover has no effect on profitability. Conclusion, cash turnover does not affect profitability, receivables turnover affects profitability. Keywords: Cash Turnover, Receivables Turnover, Profitability